Heavy and light minerals as a tool for reconstructing depositional environments: an example from the Jałówka site (northern Podlasie region, NE Poland) - Woronko, Barbara; Rychel, Joanna; Karasiewicz, Mirosław T.; Ber, Andrzej; Krzywicki, Tomasz; Marks, Leszek; Pochocka-Szwarc, Katarzyna (Geologos, 2013)
Part of northern Podlasie (NE Poland), shaped during the Wartanian stadial of the Odranian glaciation (Saalian), was situated in the periglacial zone during the Vistulian (Weichselian) glaciation. Both landforms and sediments were affected by the periglacial conditions. This is recorded at the Jałówka site, at the floor of a dry valley, where mineral deposits of 4.13 m thick, overlying organic deposits from the Eemian interglacial, were examined. These mineral deposits form four units, from bottom to top: a fluvial unit (I), a loess-like unit (II), a solifluction unit (III), and an aeolian unit with ice wedges (IV) on top of unit III. The heavy and light minerals were analysed, as well as the geochemistry, in order to find out about the parent material and to reconstruct the climatic conditions during deposition. The mineral analysis indicates that the Saalian till was predominantly derived from shallow-marine deposits; erosion accompanied by sorting of the heavy minerals took place on the basis of their mass and grain size. The original material of the till seems therefore to be sedimentary rocks from the eastern Central Baltic Basin. This material became strongly weathered under the periglacial conditions, resulting in the destruction of the quartz grains, as well as in leaching, leading to complete decalcification of the deposits. Aeolian activity resulted in infilling of ice wedges and the creation of thin layers. The intensity and the duration of these processes was limited, so that the effects of the aeolian abrasion are insignificant. Neither resulted the aeolian activity in significant reshaping of the landscape.